The travelling cat chronicles - Arikawa, Hiro, 1972-; Gabriel, Philip, 1953- (London : Doubleday, 2017)
Nana is on a road trip, but he is not sure where he is going. All that matters is that he can sit beside his beloved owner Satoru in the front seat of his silver van. Satoru is keen to visit three old friends from his youth, though Nana doesn't know why and Satoru won't say. Set against the backdrop of Japan's changing seasons and narrated with a rare gentleness and striking humour, Nana's story explores the wonder and thrill of life's unexpected detours. It is about the value of friendship and solitude, and knowing when to give and when to take.
First published in Japan in 2015.
Translated from the Japanese.
Keywords: Human-animal relationships -- Fiction; Cats -- Fiction; Automobile travel -- Fiction; Solitude -- Fiction; Japan -- Fiction; Fiction